Attitudes of Students of Different Schools of University of Zagreb on Tooth Bleaching - Dinka Diklić; Eva KLARIĆ SEVER; Nada Galić; Jelena Spajić; Katica Prskalo (Acta Stomatologica Croatica, 2016)
Objective: To compare the awareness that students from four different faculties within the University of Zagreb have of oral health and tooth bleaching procedure. Materials and Methods: The study included 158 subjects (both male and female) - 38 students from the School of Dental Medicine and 40 students from each of the following faculties: the School of Medicine, the Faculty of Economics and the Faculty of Civil Engineering. The respondents were asked to fill out the survey with multiple choices by marking the answers they considered correct. Results: Only 12% of the respondents followed the information on oral health. More than two thirds of all subjects brush their teeth twice a day, but there were no statistically significant differences between the subjects with respect to college or gender. More than half of the participants (55%) were satisfied, and 12% were completely satisfied with their dental appearance. About 80 % of the respondents were aware of differences between teeth bleaching and teeth polishing procedures, with greater prevalence among Dental Medicine and Medicine students. 80 % of all subjects would go to a dental office if they decided to whiten their teeth while less than a half (46 %) of all the subjects believed that a tooth bleaching has some adverse side-effects. Conclusions: There is a difference in knowledge on oral hygiene and tooth bleaching between the students from the School of Dental Medicine, the School of Medicine, the Faculty of Economics and those from the Faculty of Civil Engineering. Dental students have the best knowledge on tooth bleaching and oral health, which was in accordance with their educational guidance and level of education.